PENGARUH PERSEPSI HARGA, CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN AIR MINUM KEMASAN - Bangun, Rejeki; Siringoringo, Renniwaty; Suali, Suali; Simamora, Helprida (JURSIMA, 2023)
The purpose of this study was to analyze the effect of perceived price, brand image and product quality, and on purchasing decisions for packaged drinking water. The population of this research is students of the faculty of economics UNRIKA Batam totaling 105 people. The sample consists of 105 respondents, who were taken by the saturated sampling method. Data analysis using multiple regression and hypothesis testing. The results of this study concluded that perceived price has a significant effect on purchasing decisions of 0.001, brand image has a significant effect on purchasing decisions of 0.035, and product quality has a significant effect on purchasing decisions of 0.019. Perceived price, brand image and product quality simultaneously influence the decisions purchase of 0.000. Keywords: Perceived Price, Brand Image, Product Quality, Purchasing Decisions